Pengaruh Literasi Keuangan, Perilaku Keuangan, dan Pendapatan terhadap Keputusan Investasi pada Mahasiswa yang Bergabung di PT. Melia Sehat Sejahtera Lampung - Etina Wati; Isni Andriana; Kemas M. Husni Thamrin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the effect of financial literacy, financial behavior and income on investment decisions of students who join PT Melia Sehat Sejahtera Lampung. The sample in this study amounted to 74 students who were members of PT Melia Sehat Sejahtera Lampung using purposive sampling technique. The data collection technique in this study used a questionnaire. The data analysis technique in this study used multiple linear regression analysis. The data was processed using te Statisfical for product and servicer solution (SPSS) versi 22. The results showed that Financial Literacy, Financial Behavior and Income had a positive and significant effect on investment decisions for students who joined PT Melia Sehat Sejahtera Lampung